Cutaneous malignant melanoma in children and adolescents treated in pediatric oncology units. Issue 11 (27th June 2016) - Réguerre, Yves; Vittaz, Marie; Orbach, Daniel; Robert, Caroline; Bodemer, Christine; Mateus, Christina; Plantaz, Dominique; Plouvier, Emmanuel; Lutz, Patrick; Rakotonjanahary, Josue; Fraitag, Sylvie; Martin, Ludovic
Abstract: Objectives: Recent progress in the understanding of tumor biology and new targeted therapies has led to improved survival in adults with malignant melanoma (MM). MM is rare in children, especially before puberty. We report here our experience with pediatric patients with MM, describe the clinical presentation, treatment and evolution, and compare prepubescent and postpubescent disease. Methods: A retrospective, descriptive, national multicenter study was undertaken of 52 cases of MM in children and adolescents. Demographic, histopathology, treatment evolution data, and survival distributions are described. Results: Median age was 15 years (5–18). The tumors were often amelanotic (45%) and raised (83%), and Breslow thickness was greater than 4 mm in 35% of cases. Histological examination showed superficial spreading (n = 16) or spitzoid (n = 16) or nodular (n = 9) pattern. Twelve children (23%) were less than 10 years of age. The spitzoid histotype was more frequent in prepubescent children (seven of 12). Seventeen patients relapsed, of whom four had skin lesions initially diagnosed as benign. Ten patients died after relapse. Five‐year event‐free survival and overall survival were 62.7% (95% confidence interval [CI]: 45.3–76) and 75.5% (95% CI: 56.8–87.1), respectively. Conclusions: MM appears to be different in prepubescent children, of whom most had a spitzoid histotype. Diagnosis can be difficult, leading to delay in treatment. New biological tools to identify targets for treatment in MM and to differentiate spitzoid melanomas from Spitz nevi now exist. As effective targeted therapies are now available, we recommend requesting biological examination of all melanocyte‐derived skin lesions in children that could be malignant.